An empirical investigation of national innovation system of an emerging economy: A study of Malaysia / Hema Subramonian - Hema , Subramonian (2018)
This thesis examines the National Innovation System (NIS) of emerging economies using Malaysia as a case by exploring its constituents, including firms and organisations, and the national context in which they function. The NIS has been studied and applied mostly in developed economies, but only since the 1990s, there has been a focus on the emerging economies. Also, scholarly discussions on the NIS has remained overly conceptual and descriptive. Consequently, it has produced little operational or practical value. These challenges have restricted the capacity of governments to devise suitable policies to shape innovation outcomes for economic development. In light of these shortcomings, this thesis seeks to test the following hypotheses, (1) there exists an underlying hierarchical factor structure (latent constructs) of firms and national context related dimensions in firms’ innovation activities within NIS; (2) the dimensions of NIS by firm attributes and their contexts have a significant impact on innovation outcomes as enablers or as problems; and (3) the impact of NIS contextual factors on innovation outcomes is mediated by firm attributes. The study draws on a national sample and deploys a quantitative methodology to analyse the data. The Malaysian National Innovation Survey 2012 data from the Ministry of Science, Technology and Innovation is a source of the data used this thesis. The thesis uses statistical techniques associated with hybrid factor analytic models and structural equation modelling. The findings show that the NIS is a multi-dimensional and multi-level system, which comprises of sound and valid patterns or dimensions of firms and national contexts in which firms function. The structural models confirm higher explanatory power and predictive relevance in the manufacturing sector than in services. The evidence also shows that information asymmetries and ability to articulate demand emerge as systemic problems in the research. Finally, the thesis establishes that national contexts that influence innovation outcomes through firm attributes. These findings generate significant theoretical and policy implications for innovation policy. Future research can consider additional dimensions, such as social, political and historical owing to path dependency, policy owners' perspectives and further extensions to the meaning of NIS and the conduct of actors in the system.